A4IP 2025 flagship event report: Innovating agri-food research & development models for a changing landscape - Dolinga, Moritz (2025)
On October 15, 2025, the A4IP Flagship Event brought together 170 participants in Rome, and over 350 online attendees. The event explored the theme of ‘Innovating Agri-Food Research & Development Models for a Changing Landscape.’ Held under the patronage of the Italian Ministry of Foreign Affairs and International Cooperation, it convened 51 speakers representing 47 organizations—including researchers, entrepreneurs, investors, policymakers, and industry leaders—to reimagine how agricultural innovations move from laboratory discovery to real-world impact.